The coupling and coordination degree and driving mechanism of water and land resources in the Beijing-Tianjin-Hebei urban agglomeration - Weidong Chen; Meng Lian (PLoS ONE, 2025)
Against the background of sustainable development, the use and development of water and land resources have become focal topics. In this study, the entropy method, Vector Autoregression (VAR), and the coupling degree model were employed to analyze the Beijing - Tianjin - Hebei (BTH) region as a case study. The reasons and driving mechanisms for the formation of low – coupling in cities were also analyzed. The results show that except for Shijiazhuang, the overall average coupling degree of the Beijing – Tianjin – Hebei urban agglomeration showed an upward trend (the coupling degree increased from 0.415 to 0.811 from 2013 to 2022), except for Shijiazhuang. Based on the principles of the driving mechanism, the following suggestions are proposed for Shijiazhuang City: Adjust the agricultural planting structure, select drought – resistant crop varieties, and reduce the planting area of high – water – consuming crops. Revise the “Regulations on Land and Water Conservation in Shijiazhuang City” and clarify the main body responsible for land and water conservation. In the agricultural field, it is necessary to promote non – full irrigation technology and improve the utilization efficiency of irrigation water.